2006
DOI: 10.1002/dat.20046
|View full text |Cite
|
Sign up to set email alerts
|

Survey of medical students about attitudes toward organ donation

Abstract: Objective. The aim of this study was to assess and explore medical students' attitudes toward tissue and organ donation and their willingness to donate their own organs or those of a deceased relative in a setting without well-organized organ donation programs and education. Methods. Medical students from all 6 years of medical studies were surveyed using a questionnaire that included attitude and willingness measures. We also asked the medical students about the feelings they would expect to experience if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Procedure and materials. Study 2 employed the same procedure and materials as Study 1, with the only exceptions that (a) after the 3 min wait, participants also completed the Donation and Donators' Attitude Questionnaire (DDAQ; Topic, Brkljacic, & Grahovac, 2006), and (b) participants were not approached after they left the lab. In the DDAQ, participants were asked to rate (over seven items) how willing they were to donate their blood, bone marrow, skin, kidney, heart, cornea, and liver to strangers upon their death.…”
Section: Methodsmentioning
confidence: 99%
“…Procedure and materials. Study 2 employed the same procedure and materials as Study 1, with the only exceptions that (a) after the 3 min wait, participants also completed the Donation and Donators' Attitude Questionnaire (DDAQ; Topic, Brkljacic, & Grahovac, 2006), and (b) participants were not approached after they left the lab. In the DDAQ, participants were asked to rate (over seven items) how willing they were to donate their blood, bone marrow, skin, kidney, heart, cornea, and liver to strangers upon their death.…”
Section: Methodsmentioning
confidence: 99%
“…A study reported that 59% of MS would record their wish to donate organs onto electronic health cards 13 . OD card possession rates have been reported at 21-43% 9,10,20,24 . Interestingly, a study from China reported that no MS taking part held OD cards 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In Phase 2, representativeness and appropriateness of data collection were assessed by questionnaire development and evaluation, translation and back translation, pilot study, and data collection steps, whereas in phase 3, statistical analysis and statistical evidence of the construct were assessed by construct validity and reliability assessment of questionnaire items ( Figure 1). A pool of potential items was selected following a multistep process including an extensive review of relevant research papers [6][7][8][9][10] and measures both within the Arab world as well as in other parts of the world interviews with experts working in the field of organ donation or organ transplant and understanding of the theory of planned behavior [11]. In the initial phase of designing the questionnaire, items were reduced from 64 to 45 following discussions with the experts in the field of organ donation (Supplementary Materials 1 and 2).…”
Section: Methodsmentioning
confidence: 99%